Introducing the Politeness Index (PI) and Socio-Pragmatic Relational Politeness (SPRP) Model: Analysis of Politeness in Pakistani Televised Drama Qarz-e-Jaan (2024-25) - Shazia Akbar Ghilzai (Journal for Social Science Archives, 2025)
This study presented a unique mixed-method research design that explored the use of politeness in Pakistani television drama, which employed both a new quantitative tool-Politeness Index (PI), and a qualitative interpretation model-Socio-Pragmatic Relational Politeness (SPRP) Model for analyzing television content. The two models were used together to analyze four specific episodes (selected on the basis of their importance to the overall story line) of the 2024-25 Pakistan television drama series, Qarz-e-Jaan; providing researchers with data regarding the changes in how politeness is practiced over time in response to the different stages of the drama’s storyline. Results from the quantitative analysis indicated a consistent low level of Politeness Index (from 0.23 to 0.29) for each episode analyzed, indicating that there were fewer instances of explicit lexical politeness markers as compared to informal and direct expressions of communication. The qualitative analysis using the five dimensional SPRP Model (Relational Work, Cultural Frame, Emotional Display Norms, Media Staging, and Gender/Power Mediation) demonstrated that respect and relational care are most frequently expressed through contextually based, emotionally-based, non-verbally based, and culturally based practices, rather than through overtly verbalized deference. The findings challenge universalist face-saving models, demonstrate the centrality of implicit and relationally negotiated politeness in Pakistani drama, and highlight how gendered agency and moral discourse reshape traditional politeness expectations in patriarchal settings. The PI-SPRP framework offers a replicable, culturally sensitive tool for future socio-pragmatic research on South Asian media and beyond.